(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate factors affecting the health-related quality of life (HRQoL) of children with juvenile idiopathic arthritis (JIA). Subjects and Methods: A cross-sectional descriptive study was conducted on 75 children aged 5–17 years diagnosed with juvenile idiopathic arthritis (JIA) who were receiving diagnosis, treatment, and follow-up at the Department of Immunology – Allergy – Rheumatology, Vietnam National Children’s Hospital. The participants’ health-related quality of life (HRQoL) was assessed using the Pediatric Quality of Life Inventory™ 4.0 (PedsQL™ 4.0), and the associations between HRQoL and selected sociodemographic and clinical characteristics of JIA were analyzed. Results: The mean HRQoL scores of children aged 5–17 years with JIA in the domains of physical, emotional, social, school functioning, and overall HRQoL were 75.0 ± 17.98; 76.33 ± 10.37; 80.4 ± 7.70; 72.53 ± 9.59; and 75.92 ± 10.37, respectively. Conclusion: The HRQoL of children aged 5–17 years with JIA at the Department of Immunology–Allergy–Rheumatology, National Children’s Hospital, as measured by the PedsQL™ 4.0 scale, differed across age groups, with the lowest scores observed in children aged 8–12 years; however, the difference was not statistically significant. Female children had lower HRQoL scores than males in the emotional functioning domain. HRQoL scores decreased with increasing disease activity. No association was found between HRQoL and residential area.